2022
DOI: 10.1111/jfbc.14202
|View full text |Cite
|
Sign up to set email alerts
|

The effect of resistance and endurance training with ursolic acid on atrophy‐related biomarkers in muscle tissue of diabetic male rats induced by streptozotocin and ahigh‐fatdiet

Abstract: In this study, the effect of resistance and endurance training with/without ursolic acid supplementation was evaluated to identify atrophy‐related biomarkers in elderly rats induced by diabetes and a high‐fat diet (HFD) based on in silico analysis algorithms and pharmaceutical methods. The visualizer software found differential gene expression levels in skeletal muscle atrophy via computed hub gene network parameters. Also, the impact of ursolic acid, as a potent inducer of the Trp53 protein in ameliorating de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 66 publications
0
8
0
Order By: Relevance
“…In a study done by Zolfaghari et al (2022) analyzing treadmill running on diabetic Wistar rats, p53 content was found to be lower following 8 weeks of endurance training compared to the control [15]. However, within the same study, resistance training through weighted climbing did not have any observed effects on p53 levels, suggesting training modality specificity in relation to p53 protein content.…”
Section: Hypertrophymentioning
confidence: 79%
See 2 more Smart Citations
“…In a study done by Zolfaghari et al (2022) analyzing treadmill running on diabetic Wistar rats, p53 content was found to be lower following 8 weeks of endurance training compared to the control [15]. However, within the same study, resistance training through weighted climbing did not have any observed effects on p53 levels, suggesting training modality specificity in relation to p53 protein content.…”
Section: Hypertrophymentioning
confidence: 79%
“…Exercise has been extensively studied to both combat muscle atrophy and promote hypertrophy, particularly through resistance training. As well, previous research has already established a possible relationship between p53 and sarcopenia [15]. Thus, there is a natural role p53 can play when analyzing its activity during exercise-induced hypertrophy.…”
Section: Hypertrophymentioning
confidence: 80%
See 1 more Smart Citation
“…Antitumor drugs have a great contribution to muscle wasting by directly acting on muscle cells and through their systemic side effects. Zolfaghari, et al found that endurance exercise significantly modified the activity of the p53/ATF4/p21 signaling pathway [30].…”
Section: Discussionmentioning
confidence: 99%
“…Antitumor drugs have a great contribution to muscle wasting by directly acting on muscle cells and through their systemic side effects. Zolfaghari, et al found that endurance exercise significantly modified the activity of the p53/ATF4/p21 signaling pathway [ 30 ]. The results of Ashutosh, et al showed that LRRC8 complex regulates insulin-PI3K-AKT-mTOR signal in skeletal muscle, which affects the differentiation of skeletal muscle in vitro and the size of the skeletal myofiber [ 31 ].…”
Section: Discussionmentioning
confidence: 99%